Pengaturan Rangkap Jabatan Notaris dengan Anggota Dewan Perwakilan Rakyat - Halim, Bima Ridho; Sulistyarini, Rachmi (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2019)
The purpose of writing this article is to discuss the harmonization of regulation towards a double position of notary and members of the House of Representatives and the ideal formulation of regulations regarding dual notary positions. The method used is normative legal research with a statutory approach, a comparative approach, and a conceptual approach. The legal materials used are primary, secondary and tertiary legal materials which are analyzed using grammatical, systematic, interpretation, explanatory, and evaluation techniques. Harmonization of laws and regulations relating to someone who holds a concurrent position as a notary and a member of the House of Representatives is very important to meet legal certainty. The notary who is elected as a member of the House of Representatives must release his position as a notary public. Notaries can be re-becoming a notary public if they are no longer members of the House of Representatives.